Indonesian Comparative Advantage Entering the ASEAN Economic Community - Riandi Riandi; Yulius Pratomo (Universitas Negeri Malang, 2017)
The purpose of this study is to examine the comparative advantage of Indonesian commodities in order to enter the ASEAN Economic Community (AEC). This study uses the export data during the period of 2003-2013 among five ASEAN countries participating in the AEC, including Indonesia, Malaysia, The Philippines, Singapore, and Thailand. All data obtained from the UN Comtrade database following the Harmonized System (HS) at the two-digit classification level. This study applies dynamic revealed comparative advantage (DRCA) index developed by Edwards and Schoer (2001) which is the development of revealed comparative advantage (RCA) index by Balassa (1965). The results show that Indonesia is ready to enter the AEC. From this research, there are several Indonesian main commodities which have comparative advantage in ASEAN, including fish, crustaceans, molluscs, aquatic invertebrates ones (HS-03), edible fruit, nuts, peel of citrus fruit, melons (HS-08), oil seed, oleagic fruits, grain, seed, fruit, etc, nes (HS-12), lac, gums, resins, vegetable saps and extracts nes (HS-13), rubber and articles thereof (HS-40), paper & paperboard, articles of pulp, paper and board (HS-48), special woven or tufted fabric, lace, tapestry etc (HS-58), articles apparel, accessories, not knit or crochet (HS-62), and vehicles other than railway, tramway (HS-87). Those commodities are in line with Indonesian government export's strategy direction which mainly focuses on several sectors, including fishery, vegetable products, rubber, wood and wood products, textiles, and transportation. Therefore, Indonesian government should focus to improve those commodities in AEC.Keywords: Indonesian Comparative Advantage, Main Export Commodities, Export Strategy Direction, ASEAN Economic CommunityJEL Classification: F11, F43